Data Distribution Analysis of Alumni of the Civil Engineering Study Programme as a Response to LAMTEK Accreditation Standards - Nusantara, Danayanti Azmi Dewi; Risdianto, Yogie; Wulandari, Meity (Universitas Negeri Yogyakarta, 2025)
Background: A higher education quality assurance system through accreditation activities is necessary as an indicator for measuring the quality of higher education institutions to ensure that the needs of students and the community are met in accordance with established quality standards. This study aims to determine the achievements of graduates against the gold standard of Surabaya State University (UNESA), determine the time required for graduates to find their first job, evaluate the relevance of the field of study to the graduates’ fields of work, and identify the scale of their workplaces. Methods: Tracer Study data were collected from Civil Engineering undergraduate alumni graduating between 2019 to 2022. Data were gathered in 2023 through questionnaires administered through the UNESA tracer study website. The responses were analysed using quantitative descriptive methods and presented in the form of percentage-based graphs. Results: The distribution of Tracer Study data shows that the highest gold standard achievement was recorded in 2021, with 75% of alumni meeting the indicators. Regarding waiting time, more than 40% of graduates obtain their first job within three months across all years. The relevance between the field of study and the field of work reached over 40% for the ‘Very Relevant’ category, while the majority of alumni were employed in national-scale companies. Conclusion: According to the Tracer Study data distribution analysis, Unesa's Gold Standard achievement reached 75%. Furthermore, the short waiting period for employment indicates the high level of graduate readiness for the workforce. The strong relevance between academic fields of study and professional fields of work, along with the dominance of employment in national-scale companies, indicates that the Civil Engineering Study Programme at Unesa is relevant to the needs of the labor market.